Study on needle punched jute nonwoven as an artificial medium for germination of seed: Effect of bulk density. Issue 4 (19th May 2019) - Sengupta, Surajit; Debnath, Sanjoy
ABSTRACT: A uniform, porous, and bulky mechanically entangled fibrous sheet, i.e., needle-punched nonwoven, from eco-friendly and natural, low-grade jute fiber, has been designed and engineered to use as an artificial medium for germination of seed in place of soil. Needle-punched nonwoven fabrics of different bulk densities have been prepared from low-grade jute. Bulk densities of needle punched nonwoven fabric can be changed due to change of punch density, area density and depth of needle penetration. In this case, bulk densities of fabric have been achieved by varying the punch densities only, keeping the area density and depth of needle penetration same/ unaltered. As per experimentation, 500 g/m 2 area density needle punched nonwoven with 0.116 g/cm 3 bulk density shows the best quality of germination. This bulk density has been achieved using 160 punches/cm 2 and 13 mm depth of penetration as per the system applied and fiber used. It may be a good alternative as a medium of cultivation. The design of the bed is also proposed in the article. It is observed that in this artificial system, cultivation can be made in hostile condition and plant growth is better than that in soil. Its moisture-holding capacity and temperature control of medium help in better agriculture. This is highly applicable in the regions where soil is either not available or not suitable for cultivation.